Affecting User's Self-esteem: Analysis under the Self-determination Theory Perspective and Design Recommendations - Muriana, Luã Marcelo; Baranauskas, Maria Cecília Calani (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Self-esteem is a concept which refers to a person's evaluation of himself/herself that can be related to his/her success in interacting with other people and the world around them. The self-esteem of a person is built along his/her lifetime, influenced by experiences, social interactions and sense-making of the world from his/her self-perception of life. As people, technology and society are increasingly connected, technology may also influence the technology user’s self-esteem. In this paper we investigate the subject through the lens of the Self-Determination Theory, by analyzing literature work addressing the relation between technology design and self-esteem impact. As a result of this analysis, we present 18 design recommendations to digital and physical artefacts solutions based on a meta-analysis of 21 papers previously selected from literature. With these recommendations we aim at providing technical support to guide designers in improving the system towards users’ motivation and self-esteem, favoring the designer’s reflection about how the systems they develop may affect the user’s life.